Rural finance policies for food security of the poor: methodologies for a multicountry research project - Zeller, Manfred; Ahmed, Akhter; Babu, Suresh Chandra; Broca, Sumiter Singh; Diagne, Aliou; Sharma, Manohar (International Food Policy Research Institute, 1996)
The objective of IFPRI's multicountry research program on rural financial policies for food security of the poor is to identify policies and institutional arrangements that help the poor integrate themselves into sustainable savings and credit systems such that they have an increased capacity to invest, bear risk, and smooth consumption. The focus of the research on policy and program design and their effects on household investment and consumption requires field data collection at the institutional and household level. This paper presents the underlying conceptual framework and various methodological approaches that have been reviewed and tested by the team at IFPRI and at collaborating institutions. Methodologies are presented for analysis at the institutional level, mainly focusing on the determinants of the formation of financial institutions and the analysis of effects of program design on institutional conduct and performance, and at the household level, thereby addressing determinants of access to and participation in financial markets and related effects on household welfare.